Adherence to antiretroviral and cancer chemotherapy, and associated factors among patients with HIV-cancer co-morbidity at the Uganda Cancer Institute: a cross sectional study - Caroline Achieng; Nelson Bunani; Joseph Kagaayi; Fred Nuwaha (BMC, 2023)
Abstract Background Human Immunodeficiency Virus is a major global public health issue affecting millions of people, and sub-Saharan Africa where Uganda lies is disproportionately affected. There has been an increase in cancer among HIV patients which has resulted into use of co-medications that sometimes affect ART and cancer chemotherapy adherence. We aimed to determine adherence to antiretroviral and cancer chemotherapy and the associated factors among patients with HIV-cancer co-morbidity at the Uganda Cancer Institute. Methods We conducted a cross-sectional study among 200 randomly selected adult cancer patients infected with HIV and attending the Uganda cancer institute. Antiretroviral and anti-cancer chemotherapy adherence with associated factors were assessed quantitatively. We collected the data using interviewer administered semi-structured questionnaires. Modified Poisson regression with robust standard errors was used to estimate the prevalence ratios (PR) and its 95% confidence intervals (CI) for the factors associated with adherence to Antiretroviral Therapy (ART) and cancer chemotherapy. Results Overall, 54% of the study participants adhered to both ART and chemotherapy, and 55% adhered to ART while 65% adhered to cancer chemotherapy. The mean age of the respondents was 42 (SD ± 11years), and a majority, 61% were males.More than half, 56.5% were married and at least 45% had attained a primary level of education. Patients with good adherence to antiretroviral therapy and chemotherapy were 54%. No knowledge of cancer stage (PR = 0.4, 95% CI = 0.3-0.6, P < 0.0001), having an AIDS defining cancer (PR = 0.7, 95% CI = 0.5-0.9, P = 0.005), ART clinic in district not near Uganda Cancer Institute (PR = 0.7,95% CI = 0.8-1.0, P = 0.027) and affordability of cancer chemotherapy (PR = 1.4, 95% CI = 1.0-1.9, P = 0.037) were associated with adherence to both ART and cancer chemotherapy. Conclusion Adherence to both ART and cancer chemotherapy was low. Factors significantly associated with adherence were: knowledge of the cancer stage by the patient, the type of cancer diagnosis, source of ART and affordability/ availability of medications. There is a need to provide information on the stage of cancer and adherence counseling to patients. Furthermore, Integration of HIV- cancer care will be necessary for efficient and effective care for the patients.